1991
DOI: 10.1080/02652039109373969
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies on the bioavailability and disposition of bioincurred carrot residues of [14C] linuron and [14C]3,4‐dichloroaniline in rats

Abstract: Carrots grown from seed in soils spiked with [14C = O]linuron or [14C-ring]3,4-dichloroaniline (DCA), were found to contain radioactivity equivalent to 0.73 ppm linuron or 0.60 ppm DCA. After exhaustive extraction with methanol these tubers still retained 35% and 67% of the original 14C-bioincurred residues, for linuron and DCA respectively. To examine the bioavailability of these residues, rats were dosed by gavage (water vehicle) with unextracted tubers and extracted tubers. For comparison purposes 14C-spike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…For the United States as a whole, total environmental inputs of TCC from sludge recycling will be relatively higher due to the more than 18 000 treatment facilities that are in operation today. The mechanism of environmental release of TCC identified and quantified in the present study, i.e., via substantial solid phase (sludge) inputs occurring in addition to previously characterized aqueous phase inputs (4), is of potential concern because phenyl urea compounds structurally related to TCC can persist in soil, accumulate in agricultural crops (25), and also may cause secondary contamination of water resources due to surface runoff and vertical leaching in soil.…”
Section: Discussionmentioning
confidence: 89%
“…For the United States as a whole, total environmental inputs of TCC from sludge recycling will be relatively higher due to the more than 18 000 treatment facilities that are in operation today. The mechanism of environmental release of TCC identified and quantified in the present study, i.e., via substantial solid phase (sludge) inputs occurring in addition to previously characterized aqueous phase inputs (4), is of potential concern because phenyl urea compounds structurally related to TCC can persist in soil, accumulate in agricultural crops (25), and also may cause secondary contamination of water resources due to surface runoff and vertical leaching in soil.…”
Section: Discussionmentioning
confidence: 89%
“…TLC analysis of the urine revealed that approximately 75% of the radioactivity excreted in urine was unchanged lindane while the rest was depicted in two unknown compounds (1,2), the amounts of 14 C-LINDANE RESIDUES 1249 which contributed 16.5% and 8.5%, respectively. Worobey and Shields (1991) found that bioavailability was evident for most treatments, as indicated by presence of radioactivity in urine and/or in the tissues and blood of rats treated with ' 4 Clinuron and ' 4 C-3,4-dichloroaniline carrot residues. 14 C-linuron carrot residues were eliminated more rapidly via the urine than were ' 4 C-DCA carrot residues.…”
Section: Resultsmentioning
confidence: 96%
“…The primary toxic effect of 3,4-DCA is due to methaemoglobin formation by reacting with heamoglobin in blood (McMillan et al, 1991). It is absorbed from the gastrointestinal tract and through the skin and lungs (Worobey & Shields, 1991;BAuA, 2001). The transformation of propanil occurs mainly due to metabolic activity, and hence the fate of propanil in agricultural fields where it is used as a herbicide is an important area of scientific investigation.…”
Section: Introductionmentioning
confidence: 99%